Luminescent and Scintillation Properties of CeAlO3 Crystals and Phase-Separated CeAlO3/CeAl11O18 Metamaterials - Oleg Sidletskiy; Pavlo Arhipov; Serhii Tkachenko; Iaroslav Gerasymov; Georgy Trushkovsky; Tetyana Zorenko; Yuriy Zorenko; Pavel Mateychenko; Anna Puzan; Wojciech Gieszczyk; Pawel Bilski (Crystals, 2019)
This work is dedicated to the growth process and investigation of luminescent and scintillation properties of CeAlO3 single crystals and CeAlO3/CeAl11O18 metamaterials under e-beam and α-particles excitation. It has been shown that cathodoluminescence and radioluminescence spectra of CeAlO3 crystals contain two bands, peaking at 440 and 500 nm, and caused by the Ce3+ 5d−4f transitions into CeAl11O18 phase, which is present in these crystals as an admixture. Under 270 nm ultraviolet (UV) light excitation, a CeAlO3 crystal possesses complicated non-exponential luminescence decay, with the average decay time of 16 ns. The light yield of CeAlO3 crystals under α-particle excitation is about 16% and 12%, in respect to the standard Bi4Ge3O12 (BGO) crystal and Y3Al5O12:Ce (YAG:Ce) single crystalline film samples, respectively. The CeAlO3 scintillation decay is quite fast, with the decay time value t1/e in the 54−56 ns range.